Dispositional Aspects, Personality and Affects, its relationship with Satisfaction at Work - Azzollini, Susana; Perez Vilar, Pablo Sebastian (Revista Argentina de Ciencias del Comportamiento, 2012)
This paper presents the results of the literature review of 388 papers related to job satisfaction, published between 2000 and 2010. In this it shows the conclusions of different research of the importance of the dispositional, personal and emotional aspects in job satisfaction. The majority of authors recognizes the importance of these aspects in the construct, but argues that they did not entirely explain individual differences (Ilies & Judge, 2002). The revised literature notes certain correspondence between dispositional aspects and the aforementioned construct, together with the positive relationship between different aspects of the personality and affective states with job satisfaction.